Enhancement of Stability in Manet Using Proposed Algorithm - Yadav, N; Yadav, V (International Journal of Computer Sciences and Engineering, 2025)
As we know stability in ad hoc network is very much essential for soldiers during fight, So that they can send message and receive message fastly to reach their target. Mobile ad hoc network is a collection of mobile nodes. In this paper, we have simulated our proposed algorithm using MATLAB and we have analyzed our proposed algorithm using the standard performance measures such as convergence time and pause time and we have observed that the proposed algorithm is linearly scalable in terms of convergence time and convergence time is reduced as node density and pause time increases which leads to increase of stability in MANET